Sie sind auf Seite 1von 2

# mathcity.

org
Merging man and maths

Question # 1 (i)

## Exercise 6.3 (Solutions)

Textbook of Algebra and Trigonometry for Class XI
Available online @ http://www.mathcity.org, Version: 1.0.0

3 5 and 5 5

Here a = 3 5 and b = 5 5 , so
a+b 3 5+5 5 8 5
=
=
=4 5
2
2
2
(ii) Same as (i) and (ii)
A.M. =

(iii) 1 x + x 2 and 1 + x + x2

Here a = 1 x + x 2 and b = 1 + x + x 2
A.M. =

a + b 1 x + x2 + 1 + x + x 2 2 + 2 x2
=
=
= 1 + x2
2
2
2

## Question # 2 Since 5, 8 are two A.Ms between a and b.

Therefore a, 5, 8, b are in A.P.
Here a1 = a and d = 8 5 = 3
Now a2 = a1 + d 5 = a + 3 5 3 = a a = 2
Also a4 = a1 + 3d b = 2 + 3(3)

b =11

## Question # 3 Let A1 , A2 , A3 , A4 , A5 and A6 are six A.Ms between 2 and 5.

Then 2, A1 , A2 , A3 , A4 , A5 , A6 ,5 are in A.P.
Here a1 = 2 and a8 = 5
a1 + 7 d = 5 2 + 7 d = 5

7d = 5 2 7d = 3 d = 3

So A1 = a2 = a1 + d = 2 + 3 = 17
7
7
A2 = a3 = a1 + 2d = 2 + 2 3 = 2 + 6 = 20
7
7
7
A3 = a4 = a1 + 3d = 2 + 3 3 = 2 + 9 = 23
7
7
7
A4 = a5 = a1 + 4d = 2 + 4 3 = 2 + 12 = 26
7
7
7
A5 = a6 = a1 + 5d = 2 + 5 3 = 2 + 15 = 29
7
7
7
A6 = a7 = a1 + 6 d = 2 + 6 3 = 2 + 18 = 32
7
7
7
17 20 23 26 29 32
,
,
,
,
,
are six A.Ms between 2 and 5.
Hence
7 7 7 7 7 7

(
(
(
(
(

)
)
)
)
)

## Question # 4 Suppose A1 , A2 , A3 and A4 are four A.Ms between 2 and

Then

2 , A1 , A2 , A3 , A4 ,

12
are in A.P.
2

12
2
12
a1 + 5d =

Here a1 = 2 and a6 =

2 + 5d =

12
12
5d =
2
2
2

12
.
2

FSc-I / Ex 6.3 - 2

12 2
10
2
5d =
d=
2
2
2
Now A1 = a2 = a1 + d = 2 + 2 = 2 2
A2 = a3 = a1 + 2d = 2 + 2 2 = 3 2
5d =

2)
(
=
2

d= 2

A3 = a4 = a1 + 3d = 2 + 3 2 = 4 2
A4 = a5 = a1 + 4d = 2 + 4 2 = 5 2
Hence 2 2 , 3 2 , 4 2 , 5 2 are four A.Ms between

Question # 5 & 6

2 and

12
.
2

## Same as Question # 3 & 4.

Question # 7

a +b
(i )
2
a n + bn
But we have given A.M. = n1
(ii )
a + b n1
Comparing (i) and (ii)
a n + bn
a+b
=
n1
n1
a +b
2
Since we know that A.M. =

2(a n + b n ) = (a + b)(a n 1 + bn 1 )
Cross ing
2a n + 2b n = a n + a n 1 b + abn 1 + bn
2a n + 2b n a n bn = a n1 b + abn1
a n + b n = a n 1 b + abn 1
a n a n1 b = ab n1 bn
Q n = n 1+1
a n 1+1 a n1 b = abn1 b n1+1
a n 1 (a b) = bn1 (a b )
a n 1 = bn 1
a n1

=1
b n1
n1
0
0
a
a
a
=
Q =1
b
b

b
n 1 = 0 n = 1

The End